Changes in the potential distribution of invasive plant species in continental Spain in response to climate change. (4th May 2018) - Fernández de Castro, Alejandro G.; Navajas, Alicia; Fagúndez, Jaime
ABSTRACT: Background : Climate change may increase the risk of biological invasions. However, current knowledge of this interaction is limited. Aims : We aimed to quantify (1) the effect of climate change on the potential distribution of invasive plant species in Spain, (2) the importance of the area of origin of such species and (3) the vulnerability of different biogeographic provinces to future changes in climatic suitability for invaders. Methods : We applied six methods of species distribution modelling to assess the variation of climatically suitable areas for 40 alien plants. We developed a Potential Area Change Index and used it as the response variable in modelling for three future emissions scenarios and three global circulation models over three time periods. The area of origin and biogeographic province in Spain were also considered. Results : We found a highly specific response for each plant species rather than a clear trend for the entire set of species. Predicted climate suitability increased over higher emission scenarios and longer projected time lags. Neotropical species showed the greatest potential climatic range expansion. We detected a strong interaction between the geographic origin of a species and the biogeographic province. Conclusions : Special attention should be given to the areas where aridification of climate is projected and where introduced neotropical species are likely to expand their range. Future work should develop accurate species-specific approaches that allow the management invasive plant species.